Single-phase AC-AC matrix converter using Sinusoidal Pulse Width Modulation (SPWM) / Azizul Abd. Karim - Abd. Karim, Azizul (2003)
Single-Phase AC-AC Matrix Converter is a special type of Cycloconverter. Using the bidirectional switches any phase of the load can be connected to any phase of the input voltage, e.g., the zero value of the load phase voltages is maintained by connecting all the load phases to the same input phase. Using pulse-width modulation techniques, the load voltage and the load frequency are controlled from zero to their maximum values. The maximum voltage is usually close to the input voltage, but the maximum frequency can be several times that the input frequency and is only limited by practical considerations. The bi-directional switches must be capable of permitting current flow in either direction. The target of this project is to generate the Sinusoidal Pulse Width Modulation switching pattern using FPGA that is suitable to control the Single-Phase Matrix Converter. The Xilinx software is the world's largest supplier o programmable logic solutions, including industry-leading device architectures and world-class design software. It contains many enhancements and addition, one of the most significant of which is new device implementation technology. As a result this product provides hardware designers with an improved suite of tools for implementing Programmable Logic Devices.